Gut microbiota mediated hypoglycemic effect of Astragalus membranaceus polysaccharides in db/db mice - Song, Qianbo; Cheng, Sau Wan; Li, Dan; Cheng, Huiyuan; Lai, Yuen Sze; Han, Quanbin; Wu, Hoi Yan; Shaw, Pang Chui; Zuo, Zhong (Frontiers in Pharmacology, 2022)
Gut microbiota has been reported to be closely associated with Type-II diabetes. Restoration of disordered gut microbiota ecosystem has been developed into a therapeutic strategy and gradually applied on Type-II diabetes treatment with both western drugs and herbal polysaccharides. Although Astragalus membranaceus polysaccharides (AMP) have also been used to treat Type-II diabetes, no study investigated correlations between gut microbiota regulation and its hypoglycemic effect. In the present study, the role of gut microbiota on the hypoglycemic effect of AMP in db/db mice was investigated for the first time. Sixteen days treatment of AMP at the dosage of 600 mg/kg in db/db mice not only alleviated its diabetic symptoms significantly but also restored its gut microbiota community with increased production of fecal short chain fatty acids (SCFA). Our further Pearson correlation analyses revealed that the relative abundance of two intestinal bacteria, Akkermansia and Faecalibaculum, were significantly positively correlated with the hypoglycemic effect of AMP as well as fecal SCFA production. It was also noted that treatment of AMP resulted in increased secretion of glucagon-like peptide-1 (GLP-1) in serum and enhanced intestinal integrity. Further mechanistic study revealed that the increased SCFA after AMP treatment could stimulate GLP-1 secretion and improve intestinal integrity via enhancing the expression of G protein-coupled receptors 41/43 and tight junction proteins (Occudin and ZO-1), respectively, leading to the alleviation of diabetic symptoms in db/db mice.